LGTBI culture in Spanish public libraries. Dialogue on new equality laws - Gómez-Hernández, José-Antonio; Pérez-Iglesias, Javier (Anuario ThinkEPI, 2017)
The current relevance of LGTBI collections in public libraries is studied; these collections are included and prescribed in the recent laws for equality in Spanish regions such as Galicia, Catalonia, Extremadura, Madrid, Murcia, and Balearic Islands. After reflecting on the visibility of LGTBI authors and editorials, it is concluded that these collections are still scarce and that public libraries must learn about and incorporate information and documents that expand the social knowledge of sexual diversity.
Keywords: Public Libraries; Sexual diversity; LGTBI culture; Collection development; Social justice; Critical librarianship.